Biomechanical characteristics of take off action in high jump - A case study - Coh, M. (Serbian Journal of Sports Sciences, 2010)
The study aimed to establish the kinematic and dynamic parameters of the take-off action that generate the greatest efficiency in high jump. A biomechanical analysis was conducted using two synchronised cameras operating at a frequency of 50 Hz (SONY DVCAM DRS-300PK) and one high-speed camera with a 500 Hz frequency (MIKROTRON MOTION BLITZ CUBE ECO-1). The area of the last two strides of the run-up and take-off phases was defined with two Calibration Cubes measuring 1 x 1 x 2 metres. The kinematic parameters were established using the 3-D computer application APAS (Ariel Performance Analysis System). The 15-segment model of the body was digitised and defined by 18 reference points [16]. Numerical data were smoothed with a 16-level digital filter. The dynamic parameters were established using a force plate (Kistler 9287) which was fastened at the take-off zone. The horizontal (x), vertical (y) and lateral (z) components of the ground reaction forces were measured. The signal sampling frequency was 1000 Hz. It was established that the most important kinematic parameters of the high jump include the horizontal velocity of the jumper`s CM at the beginning of the take-off phase and the vertical velocity of the jumper`s CM at the end of the take-off phase, equalling 4.33 m•s-1. The efficiency of the take-off is related to the vertical ground reaction force which features two maximums. The jumper developed the first maximum of the vertical ground reaction force during the eccentric phase of the take-off, equalling 4213 N, whereas the second maximum was recorded in the concentric phase, measured at 4091 N. The lateral ground reaction force equalled 3053 N and was manifested in an extreme loading on the ankle joint of the jumper`s take-off leg in the take-off action.